(untitled) (Mugda Medical College Journal, 2025)
A cross-sectional, descriptive study was conducted between January and December of 2019, to see the utilization of the Emergency Obstetric Care (EmOC) Centers by the Forcibly Displaced Myanmar Nationals (FDMN) women. Convenient sampling technique was adopted. A total of 114 Forcibly Displaced Myanmar Nationals (FDMN) women participated in this study hailing from different FDMN refugee camps situated at Kutupalong and Balukhali of Ukhiya upazila under Cox’s Bazar district, Bangladesh. A pre-tested, semistructured questionnaire was used in this study. Data was collected through face-to-face interview of the participants and from clinical record reviews. Out of 114 respondents, most of them (34.2%) belonged to the 21-25 years age-group. About two-thirds of the respondents (63.2%) were aged below 25 years. All of respondents were married and belonged to the Muslim community. 64% of them did not complete a single year in any educational institution, while 36% studied in primary schools varying from 1 to 4 years Regarding antenatal checkup (ANC), 87(76.3%) respondents had at ANC visit, while 27(23.7%) had no ANC visit during pregnancy. Of them, 37(32.5%) had three and 22(19.2%) four or more ANC visits. Among obstetric complications, most of them (46.5%) had prolonged or obstructed labour, while 15.8% had eclampsia/preeclampsia. Other complications were: haemorrhage (12.3%); sepsis/fever (8.8%); retained product or placenta (6.1%), spontaneous abortion (6.1%) and intrauterine death (IUD) (4.4%). At EmOC centre, conservative medical treatment was provided to 47(41.2%.), while surgical treatment (Caesarean section) was performed on 21(18.4%) women. Blood transfusion was given to 11(9.6%) women. Manual removal of placenta was done on 8(7%) and removal of retained product of conception on 7(6.1%). 20(17.5%) women received assisted vaginal deliveries. Continuous assessment of the situation, planning, implementation, and further evaluation must be practiced in EmOC facilities to provide better healthcare for the Forcibly Displaced Myanmar Nationals (FDMN) women in Bangladesh. Mugda Med Coll J. 2025; 8(1): 50-54